INFLUENCE OF THE COMPLEX TREATMENT OF ARTERIAL HYPERTENSION ON THE INDICATORS OF THE SYSTEMICAL IMMUNOINFLAMMATORY ACTIVATION IN PATIENTS WITH ARTERIAL HYPERTENSION WITH OBESITY AND GOUT - Vatseba, M.O. (World of Medicine and Biology, 2019)
Arterial hypertension (AH) is a topical issue of modern health care in Ukraine, which has a significant impact on cardiovascular morbidity and mortality. Comorbidity of AH remains an insufficiently studied problem. On the background of its widespread prevalence, there is an increase in the number of people with hypertension with obesity and gout. It is important to find common pathogenetic mechanisms that would determine the development and progression of hypertension, obesity and gout. One of these is the change in the parameters of systemic immune activation (CIA). It is believed that chronic systemic inflammation causes damage to the blood vessels endothelium. As a result, the synthesis of nitric oxide stops at the vessel wall and activates the renin-angiotensin-aldosterone system (RAAS). Treatment of patients against the background of metabolic risk factors needs an aggressive therapy. Special attention is paid to antihypertensive drugs, which have a positive metabolic effect. In view of the of pathogenetic mechanisms multiplicity in combination of hypertension, obesity and gout, the therapy should also be multipurpose. Therefore, a logical and promising field is the active search for drugs, and their combinations, which can effectively influence the various stages of AH formation, in particular the indicators of Systemic immuno inflammatory activation (SIIA). The purpose of the study was to eatimate the effect of losartan and meltedonium dihydrate on the parameters of systemic immune activation in patients having essential hypertension with obesity and gout. The study involved 80 patients with essential hypertension stage II, degree 2, combined with obesity and gout. Indicators of systemic immune activation under the influence of standard therapy in the dynamics did not significantly change. Losartan on the background of standard therapy significantly lowered the level of IL-6. After 6 months of treatment, its concentration in the blood decreased by 10.81% (p